Effects of feed-withdrawal time on finishing- pig carcass characteristics and economics in a commercial environment - Frobose, H.L.; Edwards, L.N.; Prusa, K.J.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The effects of feed-withdrawal time on finishing-pig carcass composition and net returns were determined in 2 studies. In Exp. 1, a total of 728 pigs (BW = 286.4 ± 2.7 lb, 10 to 19 pigs per pen) were marketed from 48 pens that were randomly assigned to 1 of 4 treatments: feed withdrawal times of 7, 24, 36, or 48 h before harvest. Pigs were fed a common corn-soybean meal diet containing dried distillers grains with solubles (DDGS) and bakery co-products. As expected, increased feed withdrawal time decreased (linear; P < 0.001) live weight. Withholding feed also decreased (linear; P < 0.03) HCW and backfat depth. Percentage yield increased (quadratic; P < 0.01) with longer withdrawal periods, as did percentage lean (linear; P < 0.01). Withholding feed increased (quadratic; P < 0.01) live price and, accordingly, also increased (linear; P < 0.001) carcass price. These results were due in part to increased (linear; P < 0.02) premiums and decreased (linear; P < 0.01) weight discounts. Total value and net revenue received were similar (P > 0.32) between treatments as HCW decreased in fasted pigs, but feed intake per pig also decreased (quadratic; P <0.001), resulting in feed savings of up to $0.78/pig. Withholding feed for 24 h resulted in a numeric increase in net revenue of $0.89/pig compared to 7 h. In Exp. 2, the 48-h treatment was removed and replaced with a 12-h treatment in order to more accurately determine the proper time to implement feed withdrawal. The incidence of runny bung and leaking ingesta were also recorded to determine whether a relationship existed between feed withdrawal and the incidence of these processing concerns. A total of 843 pigs (BW = 273.0 lb, 16 to 26 pigs per pen) were assigned to 1 of 4 treatments: withholding feed for 7, 12, 24, or 36 h before harvest. Pigs were fed a common corn-soybean meal-based diet containing 20% DDGS. As a result of misidentification of pigs by plant personnel, data were analyzed from only 25 of the original 40 pens. Withholding feed tended to decrease (linear; P < 0.09) live weight. Unlike Exp. 1, there were no differences (P > 0.22) in HCW, percentage lean, or backfat depth across treatments. However, as in Exp.1, percentage yield (linear; P < 0.001) increased with increasing withdrawal time. Although withholding feed had no effect (P > 0.31) on the incidence of runny bung, it did increase (linear; P < 0.001) the incidence of leaking ingesta. For economics, as in Exp. 1, withholding feed increased (linear; P < 0.002) live price. Additionally, pigs that were fasted had increased (quadratic; P < 0.05) carcass price. Although premiums were similar (P > 0.32) across treatments, withholding feed decreased (quadratic; P < 0.04) weight discounts. Total value and net revenue received per pig were similar (P > 0.88) across treatments, but withholding feed decreased (linear; P < 0.001) feed intake, resulting in feed savings of up to $0.46/pig. Overall, withholding feed can be used to avoid weight discounts in heavyweight pigs without negatively impacting carcass composition and maintaining overall revenue per pig. However, these advantages come with a potential reduction in carcass weight and increased incidence of leaking ingesta, which can result in condemned heads at inspection and losses of $3 to 4 per carcass.
Keywords: Swine; Carcass; Fasting; Feed withdrawal